Refrigeration (KS13) - Terry Welch (The Chartered Institution of Building Services Engineers, 2008)
This publication will enable the reader to: — understand what the cooling requirement is— appreciate the need to minimise the cooling load— appreciate the cooling methods available today— know the operation of the vapour compression refrigeration cycle— be aware of the operation of absorption cooling systems— examine the characteristics of refrigeration systems that impact on efficiency— calculate the coefficient of performance (COP)— specify chilled water or DX systems— explain the function of the main components— be aware of the energy saving requirements of Building Regulations— be aware of refrigerant leak detection and servicing.This publication is aimed at those entering the building services industry without previous knowledge of the subject, such as graduates with mechanical, electrical or civil engineering degrees. It will also be useful for anyone without specialist experience in refrigeration. Refrigeration is sometimes seen as a 'black art' and something of a mystery, so this publication tries to unveil the workings and behaviour of refrigeration equipment applied into air conditioning for building services.